2015
DOI: 10.1111/jpn.12394
|View full text |Cite
|
Sign up to set email alerts
|

The effect of long‐term under‐ and overfeeding on the expression of six major milk proteins' genes in the mammary tissue of goats

Abstract: Milk protein synthesis in the mammary gland involves expression of six major milk proteins' genes whose nutritional regulation remains poorly defined. In this study, the effect of long-term under- and overfeeding on the expression of as1-casein: CSN1S1, as2-casein: CSN1S2, β-casein: CSN2, κ-casein: CSN3, α-lactalbumin: LALBA and β-lactoglobulin: BLG gene in goat mammary tissue (MT) was examined. Twenty-four lactating dairy goat, at 90-98 days in milk, were divided into three homogenous subgroups and fed the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Ollier et al [ 29 ], by studying the impact of 48 h food deprivation on goat mammary gene expression, found a downregulation for αs 1 and αs 2 precursors. Tsiplakou et al [ 30 ], who investigated the impact of long-term underfeeding and overfeeding on the expression of six major milk protein genes (αs 1 -casein, αs 2 -casein, β-casein, κ-casein, α-lactalbumin and β-lactoglobulin) in the mammary goat tissue, observed that underfeeding led to a decrease in the expression level of all genes, suggesting that our experimental L diet could negatively impact milk protein synthesis.…”
Section: Discussionmentioning
confidence: 96%
“…Ollier et al [ 29 ], by studying the impact of 48 h food deprivation on goat mammary gene expression, found a downregulation for αs 1 and αs 2 precursors. Tsiplakou et al [ 30 ], who investigated the impact of long-term underfeeding and overfeeding on the expression of six major milk protein genes (αs 1 -casein, αs 2 -casein, β-casein, κ-casein, α-lactalbumin and β-lactoglobulin) in the mammary goat tissue, observed that underfeeding led to a decrease in the expression level of all genes, suggesting that our experimental L diet could negatively impact milk protein synthesis.…”
Section: Discussionmentioning
confidence: 96%
“…As the MAC-T cell line is incapable of secreting milk components, milk protein content could not be detected directly in this study. The CSN2 gene expression is positively associated with milk yield [ 47 ]. Hence, the expression of casein genes may be used to evaluate milk yield as an alternative to the evaluation of casein protein synthesis in MAC-T cells [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Feeding level and nutrient availability, may affect glucose uptake and utilization in sheep [26] The effect of long term underand over-feeding on the expression of genes related to lipid metabolism [26] and major milk proteins' genes [27] in the mammary tissue of small ruminants have been described. However, little information on the effect of complete feed deprivation on gene expression of genes related to lipid metabolism in pregnant sheep is not available.…”
Section: Discussionmentioning
confidence: 99%